Replacing nitrogen by sulfur: From structurally disordered eumelanins to regioregular thiomelanin polymers - Iacomino, Mariagrazia (2017)
The oxidative polymerization of 5,6-dihydroxybenzothiophene (DHBT), the sulfur analog of the key eumelanin building block 5,6-dihydroxyindole (DHI), was investigated to probe the role of nitrogen in eumelanin build-up and properties. Unlike DHI, which gives a typical black insoluble eumelanin polymer on oxidation, DHBT is converted to a grayish amorphous solid (referred to as thiomelanin) with visible absorption and electron paramagnetic resonance properties different from those of DHI melanin. Mass spectrometry experiments revealed gradational mixtures of oligomers up to the decamer level. Quite unexpectedly, nuclear magnetic resonance (NMR) analysis of the early oligomer fractions indicated linear, 4-, and 7-linked structures in marked contrast with DHI, which gives highly complex mixtures of partially degraded oligomers. Density functional theory (DFT) calculations supported the tendency of DHBT to couple via the 4- and 7-positions. These results uncover the role of nitrogen as a major determinant of the structural diversity generated by the polymerization of DHI, and point to replacement by sulfur as a viable entry to regioregular eumelanin-type materials for potential applications for surface functionalization by dip coating.